1992
DOI: 10.2466/pr0.1992.71.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Health-Related Behavior and Quality of Life on Depressive Symptomatology in a Sample of Adolescents

Abstract: This study examined the correlations of 21 variables categorized into sociodemographic, subjective quality of life, stress, problem behavior, and health behavior predictors of at-risk and low-risk depressive symptomatology for a sample of 1056 adolescents attending public school. Discriminant function analysis showed lower life satisfaction, higher stress, and perceived unattractiveness as major discriminating variables for at-risk (CES-Depression score greater than 23) versus low-risk depressed adolescents. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 11 publications
0
16
0
3
Order By: Relevance
“…It is consistent with findings of other studies that used a variety of populations and methods. [4][5][6][7][8][9][10][11][12] Most previous studies described the association in high school students. Our study expands knowledge by describing the association in younger middle school students (aged approximately 12-14 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is consistent with findings of other studies that used a variety of populations and methods. [4][5][6][7][8][9][10][11][12] Most previous studies described the association in high school students. Our study expands knowledge by describing the association in younger middle school students (aged approximately 12-14 years).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies of adolescents showed that depression was related to a variety of unhealthy behaviors, such as cigarette smoking, 4 alcohol consumption, 5 and substance use. 6,7 In longitudinal studies, depressive symptoms in teenagers aged 15 to 16 years were positively related to the teenagers' smoking status 9 years later, 8 a previous diagnosis of major depressive disorder was 3 to 4 times more common in students with a history of alcohol abuse or substance use than in control subjects, 9 and depressed mood predicted first-time use of marijuana and other illicit drugs in secondary-school students. 10 Conversely, depressive symptoms were preceded by cigarette smoking in a large national sample of adolescents aged 12 to 18 years.…”
mentioning
confidence: 99%
“…Costello og medarbeidere (13) fant at tobakksrøyking var langt mer prevalent blant ungdom med depresjon enn blant ungdom som ikke hadde noen diagnose. Noen studier viser at sammenhengen mellom depressivitet og røyking er sterkere blant jenter enn blant gutter (14)(15)(16). Acierno og medarbeidere (17) hevder også å ha funnet dette, men de statistiske analysene de baserer denne konklusjonen på er ikke overbevisende.…”
Section: Innledningunclassified
“…17 Thus, in addressing our first question (i.e., the extent of a relationship between depressive symptoms and OSA), studies needed to include both PSG and a depression assessment measure in both the OSA and comparison groups. Twenty-two published studies were initially identified: 11 were excluded: 4 due to lack of the use of PSG to detect OSA (one lacked PSG in the control group 18 ), [19][20][21][22] 4 for the absence of a depression measure, [23][24][25][26] 1 lacked a comparison group, 27 and 1 was excluded due to division of groups into snorers versus non-snorers, without assessing for OSA. 28 Eleven studies satisfied the inclusion criteria.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…[2][3][4] Depression affects approximately 1% of preschoolers, 2% of school-aged children, and 5% to 8% of adolescents in community samples and is a risk factor for noncompliance with medical treatment. 5,6 Sleep disordered breathing (SDB) in children represents a spectrum of disorders ranging in severity from primary snoring to more severe forms such as obstructive sleep apnea (OSA).…”
mentioning
confidence: 99%